Tackling suicidal tendencies - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
When it comes to issues affecting life, mental health with the threat of increasing suicidal tendencies is becoming prevalent worldwide.This was the message that was zeroed in by the organisers of the World Suicide Prevention Day when they launched the “40 seconds of action” campaign “to raise awareness of the scale of suicide around the world and the role that each of us can play to help prevent it”.